The influence of macroeconomic factors on Malaysia stock market performance / Nur Amirah Nabilah Mohd Taufek - Mohd Taufek, Nur Amirah Nabilah (2022)
The research of the macroeconomic factors for stock market performance has been widely documented for years. The purpose of the study is to analyze the influence of the macroeconomic factors on Malaysia's Stock Market Performance between period January 2012 to December 2021 on monthly basis. The total that has been observed from this study is 10 years. This research uses selected four independent variables which are Gross Domestic Product (GDP), Inflation Rate, Interest Rate and Exchange Rate while the dependent variable is Kuala Lumpur Composite Index (KLCI). In addition, this research is utilizing descriptive analysis, correlation analysis, multicollinearity test and regression analysis to determine either the independent variable is significant or insignificant towards KLCI. Research finding has shown that all independent variable have significant relationship with Malaysia Stock Market Performance (KLCI Index) thus the null hypothesis is rejected.